Aggressive Colorectal Cancer in an Inflammatory Bowel Disease Patient following Treatment with Vedolizumab: A Case Report - Nascimento,Catarina (2022)
Abstract Introduction: The increased risk of bowel cancer in patients with inflammatory bowel disease can be related with the extent, duration and severity of inflammation or with the cancer immune surveillance interference of immunosuppressive drugs used in inflammatory bowel disease treatment. Therefore, the risk-benefit ratio associated with long-term therapeutic strategies should be based on the patient’s age, sex, comorbidities and disease phenotype. Case Report: We present the case of a 76-year-old man with a history of melanoma stage Clark III and steroid-dependent left-sided colitis, refractory to mesalamine and thiopurines, with a diagnosis of a multifocal colorectal adenocarcinoma shortly after clinical and endoscopic remission 1 year after starting vedolizumab. Discussion: Vedolizumab is a gut-selective monoclonal anti-α4β7-integrin antibody that inhibits lymphocyte migration into the gastrointestinal submucosa. Its effectiveness for induction and maintenance of remission and its favorable safety profile make it an alternative in patients with chronic refractory colitis and contraindications to anti-TNF-α. However, there is the hypothesis that, by reducing the migration of activated leukocytes to the gastrointestinal tract, it may also reduce immunosurveillance, increasing the colorectal malignancy risk in the long term. More studies are necessary to address this issue.